KECERDASAN DALAM PANDANGAN ISLAM - Wirdatul Hasanah; Siti Muthiatun Najiyah; Siti Aminah; Suniati; Diah Ainun Khafidloh; Titin Nurhidayati (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
Intelligence is a gift from Allah SWT that distinguishes humans from other creatures. In Islam, intelligence is not limited to intellectual ability but also includes spiritual, emotional, and moral aspects. Islam views intelligence as a means to know Allah SWT, understand His creations, and fulfill human responsibilities as khalifah (stewards) on earth. This paper aims to examine the concept of intelligence in Islam, its types, and the role of intelligence in shaping faithful and moral individuals.